A study about the 3D acceleration in front crawl and its relation with performance - Tella, V.; Madera, J.; Colado, J. C.; Mateu, J.; Garcia Masso, X.; Gonzalez, L. M. (Biomechanics and Medicine in Swimming XI, 2010)
The objective of this study was to analyze the acceleration generated during front crawl. The swimmers (n=70) performed 25 meters at maximum velocity. 3D accelera-tion (ms-2) was registered. Root Mean Square (RMS) was calculated in the anterior-posterior (X), medium-lateral (Y) and upper-lower (Z) direction. RMS indexes were calculated to relate the directions in twos. One-way ANOVA was performed. Relations between variables have been calculated with Pearson`s r. The results show differences (p<0,01) between RMSX (1,71±0,05), RMSY (4,92±0,17) and RMSZ (2,30±0,12). Velocity correlated positively RMS values (p<0,01) and the indexes that relate the RMSX with RMSY (p<0,01) and RMSZ (p<0,01). To conclude, 3D acceleration analysis might indicate the efficiency during front crawl.